Trade remedy measures and their effects on industry performance, and implicit government intentions: Changes in revealed comparative advantage indices in China, India, and Japan - Keiichi Iwase; Shuichi Ishida (Journal of Government and Economics)
This study introduces a two-dimensional matrix analysis method that utilizes revealed comparative advantage and revealed comparative disadvantage indices. It aims to clarify the impact of trade remedy measures on beneficiary industries' performance. We compare the effects of these measures across both growing and mature industries. In the former case, we examine the steel industries in China and India, while in the latter case, we focus on Japan's basic chemicals and other products. By tracking the changes in the revealed comparative advantage and disadvantage indices before and after the execution of each measure, we identify distinct patterns depending on the industry's developmental stage. Although trade remedy measures are defined as countermeasures against unfair trade practices, this distinction enables us to determine whether trade remedy measures serve as tools for enhancing and sustaining industrial competitiveness or averting competitive disadvantages effectively with implicit intentions of governments. Furthermore, this analytical framework also provides insights into industry conditions. Its versatility extends to potential applications in corporate management and policy evaluation.